Repeated Transcranial Direct Current Stimulation Induces Behavioral, Metabolic and Neurochemical Effects in Rats on High-Calorie Diet - Ziomber, Agata; Rokita, Eugeniusz; Kaszuba-Zwoinska, Jolanta; Romańska, Irena; Michaluk, Jerzy; Antkiewicz-Michaluk, Lucyna (Frontiers in Behavioral Neuroscience, 2018)
Due to its high prevalence, obesity is considered an epidemic, which stimulated research on non-invasive methods to reduce excess body fat. Transcranial direct current stimulation (tDCS) is a non-invasive technique used to modulate the activity of cerebral cortex, which has already found increasing interest in medicine as a promising methodology. The aim of this study was to analyze the impact of tDCS on feeding behavior, metabolic abnormalities and neurotransmitters in certain brain areas involved in appetite control of obese rats. The male Wistar rats were divided into five subgroups depending on an effect of consumed diet (lean, obese) and tDCS type (anodal, cathodal, sham, and no stimulation). Two 10-min daily sessions of tDCS for eight consecutive days of the study were applied. Rats subjected to active tDCS (anodal right or cathodal left of the prefrontal cortex) had reduced appetite and showed lesser body weight gain than the animals subjected to sham procedure or those receiving no stimulation at all. Furthermore, tDCS contributed to reduction of epididymal fat pads and to a decrease in blood concentration of leptin. Neurochemical examination revealed that tDCS modulated serotonin pathways of the reward-related brain areas and contributed to a significant decrease in the density of D2 but not D1 dopamine receptors in the dorsal striatum, recorded 5 hours after the last stimulation. No significant effect of tDCS on dopamine and it’s metabolites in examined brain regions was observed. It seems that the hypothalamus was not affected by tDCS application as no changes in measured neurotransmitters were detected at any examined time point. However, these results do not exclude the possibility of the delayed response of the monoamines in the examined brain areas to tDCS application. Altogether, these findings imply that repeated tDCS of the prefrontal cortex may change feeding behavior of obese rats. Either right anodal or left cathodal tDCS were sufficient to decrease food intake, to reduce body adiposity and to normalize other metabolic anomalies. These beneficial effects can be at least partially explained by changes in serotoninergic and in lesser extent dopaminergic system activity within some brain areas belonging to reward system.